A novel splice site mutation in anthrax toxin receptor 2 (Capillary morphogenesis protein 2) gene results in systemic hyalinosis - Indhra Priyadharshini; Sirisha Varala; Tallapaka Karthik Bharadwaj; Ananthula Venkata Krishna (Wolters Kluwer Medknow Publications, 2022)
Infantile Systemic Hyalinosis, now included under the unifying term, "hyaline fibromatosis syndrome" (HFS) is a rare, progressive and fatal autosomal recessive disorder characterized by various dermatological manifestations such as thickened skin, papules and nodules, hyperpigmentation over bony prominences, gingival hypertrophy and systemic manifestations such as joint contractures, osteopenia, recurrent infections, diarrhea, and short stature. Histopathological examination of the affected tissue shows deposition of amorphous hyaline material. Mutations in the gene encoding capillary morphogenesis protein-2/anthrax toxin receptor 2 (ANTXR2) are implicated in the pathogenesis. Here, we report a 16-month-old toddler with HFS whose genetic analysis revealed a novel homozygous frameshift mutation in exon 13 of ANTXR2 gene.